Sinus Floor Elevation with Modified Crestal Approach and Single Loaded Short Implants: A Case Report with 4 Years of Follow-Up. (18th December 2017) - Perelli, Michele; Abundo, Roberto; Corrente, Giuseppe; Saccone, Carlo; Arduino, Paolo G.
Abstract : Tooth extraction is usually followed by bone reduction. In the maxillary posterior region, this remodelling combined with sinus pneumatisation and periodontal defects may lead to a reduced basal bone height available for implant placement. Sinus floor elevation can be performed with different surgical techniques. Crestal approach has demonstrated to be effective, less invasive, and associated with a reduced morbidity. This article reports a modified sinus floor elevation by means of rotary, noncutting instruments, addition of xenograft, and 2 short-threaded implant placements. The aim of the study was to evaluate the implant's success and intrasinus radiographical bone gain after 4 years of functional loading. The premolar implant site presented a starting basal bone height of 6 mm, while the molar site was of 2 mm. In the first surgical step, sinus floor elevation was performed mesially and the implant was inserted, and distally only sinus floor elevation was performed. After 6 months, the mesial implant was uncovered and the second implant was inserted; 4 months later, the second fixture was uncovered, and both fixtures were loaded with single provisional screw-retained crowns and later with single screw-retained porcelain fused to metal crowns. Implants integrated successfully, and crestal bone remodelling did not exceed the smooth collar. Bone gain was 3 mm for the mesial implant and more than 5 mm for the distal one.